2019
DOI: 10.3390/app9071466
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Magnetic Fields on Quench Characteristics of Superconducting Tape for Superconducting Fault Current Limiter

Abstract: In DC systems, DC resistive type superconducting fault current limiters (R-SFCLs) can respond within a few hundred milliseconds and limit the fault current to a very low level to protect the power equipment in DC systems. The main part of R-SFCLs are superconducting tapes. When short-circuit faults occur in the system, the superconducting tapes will quench and become a large quenched resistor to limit the fault current. The surrounding magnetic fields and the magnetic fields caused by the superconducting tapes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The YBCO superconducting tapes used in the experiments were produced by SST [39]. Al 2 O 3 /Y 2 O 3 /MgO/LaMnO 3 /CeO 2 /REBCO/Ag layers were successively plated on 50 µm thick 10 mm wide Hastelloy TM substrate.…”
Section: Experimental Details 21 Preparation Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The YBCO superconducting tapes used in the experiments were produced by SST [39]. Al 2 O 3 /Y 2 O 3 /MgO/LaMnO 3 /CeO 2 /REBCO/Ag layers were successively plated on 50 µm thick 10 mm wide Hastelloy TM substrate.…”
Section: Experimental Details 21 Preparation Of Samplesmentioning
confidence: 99%
“…Extensive studies have been carried out on testing HTS tapes for resistive fault current limiter application. Llambes et al [25] and Hajdasz et al [26] studied the application of superpower tapes in SFCL; Schmidt et al [27] and Baldan et al [28,29] studied the application of AMSC tapes in SFCL; Ahn et al [30], Park et al [31], and Sheng et al [32] compared the tape structures from different postprocessing treatments in the application of SFCL; Lacroix et al [33,34] developed a novel structure to increase the NZPV (normal zone propagation velocity) of HTS tape during impulse impact; Zhang et al [35] and Liu et al [36] determined the DC overcurrent impact on the tapes at different temperatures and analyzed quench resistance; Sheng et al [37] and Maeda et al [38] studied the quench recovery of the tapes after overcurrent impact and observed the bubbles generated by heat transfer on the tape surface during the quench process; Xiang et al [39] studied the effect of magnetic field on the overcurrent impact of tapes; Rusi ński et al [40] and Jiang et al [41] studied the effect of tape insulation on overcurrent impact; Liang et al [42,43] modeled the quench resistance of the tape through the R-Q curve; LV et al [44] laminated the optical fiber on the side of the tape to measure the temperature during the overcurrent impact process.…”
Section: Introductionmentioning
confidence: 99%